تأثير الفطر Trichoderma harzianum في إصابة نبات التبغ (صنف البرلي) بمرض الساق الأسود الناتج عن الفطر Phytophthora parasitica var. nicotianae - حسن, محمود; محمد, رامز; حسن, طارق (Latakia University Journal -Biological Sciences Series, 2018)
To Study the influence of fungus Trichoderma harzianum against the fungus Phytophthora parasitica var nicotianae the causal agent of tobacco black shank disease in the laboratory and the field. We found the inhibition growth percent of P. parasitica var nicotianae by T.harzianum by 58.42% , in the field the infection percent of tobacco burley plant which treated with T. harzianum was decreased to 18.8% by the spray method, and 50% by the irrigation method comparing with the control which infected by P. parasitica. var nicotianae was 53.3%, and decreased the infection severity to 59.1% and 73.3% respectively for treated plants by T. harzianum by spray and irrigation method comparing by the infection severity of control which was 50.8%. The concentration of Free Salicylic Acid in treated plant by both fungi was 104 and 106.3 ppm in the plants which treated by T. harzianum by spray and irrigation method respectively, and 62 ppm to the control which treated by P.p var nicotianae. And the Peroxidase activity reached to 1.08 and 1.16 respectively nanomol in the treated plants by T.harzianum by spray and irrigation method sequentially comparing by 0.68 nanomol in the control which treated by P.p var nicotianae. So we noticed the positive role of T.harzianum by decreased percent and severity infection of black shank disease , we refer this to its role in stimulate the Aquired Systemic Resistance by measured free salicylic acid and Peroxidase activity in treated plants. تمَّ دراسة تأثير الفطر Trichoderma harzianum ضد الفطر المسبب لمرض الساق الأسود Phytophthora parasitica var. nicotianae مخبرياً وحقلياً. ,وجد أن نسبة منع فطر T. harzianum للفطر الممرض P. parasitica var. nicotianae مخبرياً 58.42 %. أما حقلياً فخفض من نسبة إصابة نباتات التبغ البرلي المعاملة بفطر T. harzianum بطريقة الرش إلى 18.8 % و50% بطريقة الري مقارنة بالشاهد المعدى بالفطر P.p var. nicotianae الذي وصلت فيه نسبة الإصابة إلى 53.3% , وخفض من شدة الإصابة إلى 59.1% للنباتات المعداة بالفطرT. harzianum بطريقة الرش و 73.8% بطريقة الري مقارنة بالشاهد المعدى بالفطر الممرض الذي وصلت فيه شدة الإصابة إلى 50.8%. وبتحليل كمية حمض الساليسيليك الحر الموجود في النباتات المعاملة بكلا الفطرين وجدنا ارتفاع في تركيز حمض الساليسيليك الحر إذ وصل إلى 104و 106.3 PPM في النباتات المعاملة بالفطر T. harzianumبطريقة الرش والري على التوالي, مقارنة ب 62 PPM للشاهد المعدى بالفطر الممرض.كما وجدنا ارتفاع في مستوى نشاط إنزيم البيروكسيداز وصل إلى 1.08 و 1.16 نانو مول في النباتات المعاملة بالفطر T. harzianum بطريقتي الرش والري على التوالي مقارنة ب 0.68 نانو مول في النباتات المعداة بالفطر الممرض. وهنا نلاحظ الدور الايجابي للفطر T. harzianum في تخفيض نسبة وشدة الإصابة بمرض الساق الأسود ويمكن أن يعزى دوره في تحفيز المقاومة الجهازية المكتسبة من خلال قياس حمض الساليسيليك الحر وإنزيم البيروكسيداز في النباتات المعاملة.